PENGARUH PENDAPATAN ASLI DAERAH DAN DANA BAGI HASIL SERTA DANA ALOKASI KHUSUS TERHADAP KEMANDIRIAN DAERAH KABUPATEN PASER - Muhammad Jarkasih; Eny Rochaida; Sri Wahyuni (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to analyze the influence of Local Own-Source Revenue (PAD), Revenue Sharing Funds (DBH), and Special Allocation Funds (DAK) on the regional independence of Paser Regency. Based on the analysis results, it was found that PAD has a positive and significant effect on regional independence, meaning that the higher the PAD, the greater the level of regional independence. Conversely, DBH has a negative and significant effect, indicating the region’s dependence on fund transfers from the central government. Meanwhile, DAK has no significant effect on regional independence due to its nature of being tied to specific projects. The study suggests that the Paser Regency government optimize PAD through mapping local sector potential, digitizing regional financial systems, and maximizing regional assets. In addition, strengthening the role of Regional-Owned Enterprises (BUMD), advocating for fairer central government transfer policies, and ensuring well-targeted DAK management are also needed to enhance regional independence. Regular evaluation and monitoring using Key Performance Indicators (KPIs), along with improving the capacity of government officials, are expected to support more effective regional financial management.